HOPE in action: A prospective multicenter pilot study of liver transplantation from donors with HIV to recipients with HIV. Issue 3 (25th November 2021) - Durand, Christine M.; Florman, Sander; Motter, Jennifer D.; Brown, Diane; Ostrander, Darin; Yu, Sile; Liang, Tao; Werbel, William A.; Cameron, Andrew; Ottmann, Shane; Hamilton, James P.; Redd, Andrew D.; et al.
Abstract : Liver transplantation (LT) from donors‐with‐HIV to recipients‐with‐HIV (HIV D+/R+) is permitted under the HOPE Act. There are only three international single‐case reports of HIV D+/R+ LT, each with limited follow‐up. We performed a prospective multicenter pilot study comparing HIV D+/R+ to donors‐without‐HIV to recipients‐with‐HIV (HIV D−/R+) LT. We quantified patient survival, graft survival, rejection, serious adverse events (SAEs), human immunodeficiency virus (HIV) breakthrough, infections, and malignancies, using Cox and negative binomial regression with inverse probability of treatment weighting. Between March 2016–July 2019, there were 45 LTs (8 simultaneous liver‐kidney) at 9 centers: 24 HIV D+/R+, 21 HIV D−/R+ (10 D− were false‐positive). The median follow‐up time was 23 months. Median recipient CD4 was 287 cells/µL with 100% on antiretroviral therapy; 56% were hepatitis C virus (HCV)‐seropositive, 13% HCV‐viremic. Weighted 1‐year survival was 83.3% versus 100.0% in D+ versus D− groups ( p  = .04). There were no differences in one‐year graft survival (96.0% vs. 100.0%), rejection (10.8% vs. 18.2%), HIV breakthrough (8% vs. 10%), or SAEs (all p  > .05). HIV D+/R+ had more opportunistic infections, infectious hospitalizations, and cancer. In this multicenter pilot study of HIV D+/R+ LT, patient and graft survival were better than historical cohorts, however, a potential increase in infections and cancer merits further investigation. Abstract : A multicenter study of HIV+ donor to HIV+ recipient liver transplantation under the HOPE Act shows that patient and graft survival were better than historical cohorts, but the possible increased incidence of infections and cancer merits further investigation.